Globalisasi Dan Tantangan Kebangsaan Dalam Menjaga Identitas Nasional Serta Keutuhan Negara Di Era Modern Yang Serba Terbuka - Elma Astuti, Naima; Sutriani, Liza; Anugrah, Raihan Dwi; Wardah, Nafiatul (JPT : Jurnal Pendidikan Tematik, 2024)
We are currently in an era that must be confronted. The question of "what does it mean to be Indonesian" is frequently asked. The world is increasingly integrated in a globalization, which entails fundamental changes in our lives. Economic systems are inextricably linked. Even diverse cultures can be traced, and political systems are frequently encountered. In the past, politics may have been limited to choosing leaders or domestic policies. Now, global political decisions such as international trade agreements, technology regulations, or political pressure from superpowers directly affect the price of basic necessities in the market, employment opportunities, and even the rule of law within our own countries. We understand the impact of these systems from different perspectives. From this perspective, this research was conducted to explore more deeply how globalization is reshaping Indonesia, without forgetting its national identity. And how do our noble values ​​survive amidst the onslaught of global values? How does the local economy compete in the international arena? And most crucially, how does our political system respond to all these changes? This research employs a qualitative descriptive research method through a literature review of various scientific sources at the national and international levels.